Immobilization of streptavidin on a plasmonic Au-TiO2 thin film towards an LSPR biosensing platform - Pereira-Silva, Patrícia (2022)
Optical biosensors based on localized surface plasmon resonance (LSPR) are the future of label-free detection methods. This work reports the development of plasmonic thin films, containing Au nanoparticles dispersed in a TiO2 matrix, as platforms for LSPR biosensors. Post-deposition treatments were employed, namely annealing at 400 °C, to develop an LSPR band, and Ar plasma, to improve the sensitivity of the Au-TiO2 thin film. Streptavidin and biotin conjugated with horseradish peroxidase (HRP) were chosen as the model receptor–analyte, to prove the efficiency of the immobilization method and to demonstrate the potential of the LSPR-based biosensor. The Au-TiO2 thin films were activated with O2 plasma, to promote the streptavidin immobilization as a biorecognition element, by increasing the surface hydrophilicity (contact angle drop to 7°). The interaction between biotin and the immobilized streptavidin was confirmed by the detection of HRP activity (average absorbance 1.9 ± 0.6), following a protocol based on enzyme-linked immunosorbent assay (ELISA). Furthermore, an LSPR wavelength shift was detectable (0.8 ± 0.1 nm), resulting from a plasmonic thin-film platform with a refractive index sensitivity estimated to be 33 nm/RIU. The detection of the analyte using these two different methods proves that the functionalization protocol was successful and the Au-TiO2 thin films have the potential to be used as an LSPR platform for label-free biosensors.